Utility of extended HPV genotyping in cervical cancer screening: a prospective population-based cohort study in China - Yi, Kexin; Zhang, Jinyu; Wang, Hong; Chen, Peipei; Sun, Xingyuan; Li, Mengjie; Zhang, Shaokai (Frontiers in Oncology, 2026)
BackgroundCervical cancer poses a substantial global health burden, particularly in China where it contributes substantially to incidence and mortality. Conventional HR-HPV screening tests primarily target HPV16/18, limiting efficacy in regions dominated by other oncogenic genotypes and underscoring the need for extended genotyping to refine risk-stratified approaches.MethodsThis prospective cohort in Henan Province, China (2017–2020), enrolled 3,299 women aged 21–64 for baseline HR-HPV testing using an extended genotyping assay detecting 14 types and identifying HPV16/18/33/52/58. HR-HPV-positives were followed annually, negatives at year 3. Three-year cumulative CIN2+/CIN3+ risks, sensitivity, specificity, PPV, and NPV were computed independent of cytology.ResultsBaseline HR-HPV positivity was 18.3%. Over 3 years, 98 CIN2+ and 60 CIN3+ cases were detected. Absolute CIN2+ risks was highest for HPV16 (32.8%), comparable for HPV18/33/58 (25–28%), with relative risks exceeding 96-fold compared to HR-HPV-negatives. Extended genotyping for HPV16/18/33/52/58 improved CIN2+/CIN3+ sensitivity to 55.1% and 60.0%, respectively (vs. 51.0% and 53.3% for HPV16/18), while maintaining specificities >93%.ConclusionsIn Chinese women, non-16/18 high-risk genotypes exhibit risks comparable to HPV16/18, emphasizing the value of extended genotyping in enhancing risk-based screening sensitivity and efficiency in high-burden contexts.